PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR MATERI KESELAMATAN DAN KESEHATAN KERJA (K3) PADA SISWA KELAS X APHP UPT SMK NEGERI 8 PINRANG - Askar; Suardi Zain; Firman; Jusman Tang (STKIP Subang, 2026)
Askar, 2026. The Effect of Project Based Learning (PjBL) Learning Model on the Learning Outcomes of Occupational Safety and Health (K3) Materials in Class X Students of SMK Negeri 8 Pinrang was supervised by Suardi Zain and Firman. This study aims to determine the influence of the Project Based Learning (PjBL) learning model on learning outcomes in Occupational Safety and Health (K3) materials for students in class X APHP UPT SMK Negeri 8 Pinrang. This study uses a quantitative approach with a pre-experimental type and a one group pretest-posttest design. The sample in this study amounted to 13 students who were selected by the total sampling technique. The instrument used is a learning outcome test consisting of a pretest and posttest. The results of the descriptive statistical analysis showed that the average value (mean) of the pretest was 45.0769 with a minimum value of 30 and a maximum of 57. After being given treatment using the Project Based Learning (PjBL) learning model, a mean posttest score of 83.9231 was obtained with a minimum score of 77 and a maximum of 94. These results show an increase in student learning outcomes after the implementation of the Project Based Learning (PjBL) learning model. Thus, it can be concluded that the Project Based Learning (PjBL) learning model has a positive effect on student learning outcomes in Occupational Safety and Health (K3) materials.